Food Insecurity and Its Relationship with Food Intake and Demographic Factors in Pregnant Women in Tehran - Mina Hajihosein; Shahryar Eghtesadi; Ariyo Movahedi (Journal of Nutrition and Food Security)
Food security is described as physical and economic access for all people at all times to sufficient food for an active and healthy life. The purpose of this study was to investigate the prevalence of food insecurity and its relationship with the health status of pregnant women referred to North Tehran Health Center. Methods: The current study is a cross-sectional study conducted on 160 pregnant women in the third trimester covered by North Tehran Health Center in 2017-2018. Food security status, and dietary intake were assessed using general demographic and socioeconomic questionnaires, USDA 18-item household food security, and semi-quantitative food frequency recall, respectively. Statistical analysis was performed using SPSS and nutritionist IV software. Significance level was set at 0.05. Results: The study showed that 21.8% of mothers suffered insecure nutritional status and 78.2% of them were in safe nutritional status. There was a significant difference (P=0.013) between the two category of food groups (P=0.013). The mean consumption of legumes in people with insecure nutrition status (65.72±42.40 g) was more than nutrition secure group (50.08±29.77 g). Other food items showed no significant difference between the two groups of safe and unsafe nutrition status. In terms of economic status, there was a significant difference between safe and unsafe groups (P=0.001). Conclusion: In this study, food insecurity rate and prevalence of pregnant women was much less than that other studies. Given the role of the economic situation in the ability to purchase and supply food, probably one of the main reasons of more consumption of legumes in insecure groups would be low-income level and lower purchasing power of other food groups, such as meat.